ANALISIS TINGKAT KESEHATAN KEUANGAN PERUSAHAAN BUMN: Studi Kasus Pada Perum LPPNPI AirNav Indonesia - Niza, Triska Anggun Choirun; Choerudin, Achmad; Husin, Syahri Al (Gapenas Publisher, 2025)
In the provision of flight navigation services in accordance with applicable standards to achieve efficiency and effectiveness of flight within the national and international scope of Perum LPPNPI. However, during the 2 years of the COVID-19 pandemic, AirNav was greatly affected by the decrease in the number of flight traffic. It can be seen from the growth of Indonesia's economy which crawled up in general at the end of 2021, the Ministry of State-Owned Enterprises (SOEs) stated that all SOEs recorded healthier financial performance growth. This study aims to find out the level of financial health of LPPNPI AirNav Indonesia after the COVID-19 pandemic in 2021-2023 based on the Decree of the Minister of SOEs Number: KEP-100/MBU/2002, and the strategy to improve financial health carried out. This research is descriptive quantitative, using secondary data from LPPNPI AirNav Indonesia's financial report for the 2019-2021 period. The results of the study explain that the level of financial health of Perum LPPNPI AirNav Indonesia has a poor level of financial health, and companies must utilize in-depth financial data analysis to determine priorities, digital transformation of business processes, including air navigation systems and internal management, is also an important element in supporting financial performance